Evaluation of Nonconformity To Pedestrian Safety Measure in Immediate Area of LRT Cawang-Dukuh Atas Construction Site - Susy Fatena Rostiyanti; Seng Hansen; Pratama H Siregar; Zevinska Jodie (Jurnal Rekayasa Sipil (JRS-Unand), 2020)
The practice of providing safe temporary facilities for pedestrians during the execution of infrastructure projects is still challenging due to project complexity and the management of existing traffic flow. The challenge of ensuring pedestrian safety also becomes a concern in Jakarta, Indonesia, which currently has many ongoing infrastructure projects. The execution of these projects along existing main roads demands contractors to close some road lanes including pedestrian accesses. The circumstance highlights the importance of investigating the current practice in providing safe temporary pedestrian access. This study aims to investigate the safety and comfort measure of pedestrian access adjacent to the construction site. Nonconformities to safety findings from the field later are used as a basis for expert interviews in order to acquire recommendations. This research took a case study of the Light Rail Transit (LRT) project with a section length of 3.6 km. Observations took place every 100 meters and all nonconformities to safety data were recorded. Findings showed that among the potential nonconformities to safety, only six of those factors occurred frequently which later became the basis of questionnaire development for semi-structured expert interviews. Three experts from different backgrounds were chosen. Content analysis was used to analyze the data. Field observation result shows that among the six factors of nonconformity to safety, the unavailability of the separator system between the pedestrian access and road lane becomes the most occurred factor. The research demonstrates that in order to provide safety for pedestrians, access should be prepared with a minimum width of 90-100 cm, durable and stable surface, as well as a barrier that ensures safety against traffic and construction work. This study recommends the practical considerations for pedestrian safety as well as policies in terms of contractor’s organization and government in a broader perspective.